Darwin's Tubercle: Review of a Unique Congenital Anomaly. Issue 2 (June 2016) - Loh, Tiffany; Cohen, Philip
Abstract Background "Darwin's tubercle" is a term used to describe an atavistic swelling of the posterior helix that is present in some individuals. Little is known about its prevalence, characteristics, and function. With growing interest in the individuality of external ear patterns and its possible applications to personal identification, more knowledge about this tubercle is warranted. Purpose We review the history, clinical presentation, and modern-day influences of Darwin's tubercle. Method A comprehensive review of the literature was performed. Pubmed was searched with the key words: auricle, congenital, Darwin, ear, evolution, helix, pinna, tubercle, Woolnerian. Result Darwin's tubercle has been documented to be present in about 10.5% of the Spanish adult population, 40% of Indian adults, and 58% of Swedish school children. It has a variety of clinical presentations, which may be classified by its degree of protuberance. The influence of genetics on the expression of Darwin's tubercle is unclear, and there are conflicting observations about its correlations with age and gender. Although usually present bilaterally in individuals who do possess this trait, a portion of this population does display asymmetric expression. Conclusion Darwin's tubercle is a benign and unique helical feature. It contributes to the individuality of human ears and may have applications toward personal identification in the future.